Anti-apoptosis Effect of Gualou Guizhi Granule on Neurons in Ischemic Stroke Rats and Primary Hippocampal Neurons - Yu LIN; Wei XU; Yuqin ZHANG; Huang LI; Wen XU (康复学报)
Objective:To investigate the anti-apoptosis effect of Gualou Guizhi granule(GLGZG)on neurons in ischemic stroke rats and primary hippocampal neurons, and then explore the involved protective mechanism of GLGZG, thus providing a theoretical basis for the treatment of stroke.Methods:Glutamate-induced primary hippocampal neurons excitotoxicity injury model and focal cerebral ischemic-reperfusion injury model were established. MTT and LDH assay were used to detect the effect of GLGZG on primary hippocampal neurons and LDH activity. At the same time, Western Blot and Real-time PCR were used to detect the effect of GLGZG on gene expressions of Caspase-3, Bcl-2 and Bax mRNA in primary hippocampal neurons as well as the protein expressions in hippocampus tissues of rats.Results:The hippocampal neuron cells were treated with different concentrations of GLGZG(100 μg/mL, 200 μg/mL, 300 μg/mL)for 24 hours, the cell viability increased(P<0.05, P<0.01)and the LDH activity significantly reduced (P<0.05, P<0.01) in the above three GLGZG groups in comparison with that in the glutamate group. The cell viability were significantly improved, while the release of glutamate-induced injured neurons LDH could be significantly suppressed in the group at a dose of 200 μg/mL and 300 μg/mL(P<0.05, P<0.01). After the treatment with GLGZG, the down-regulated expression of Caspase-3, Bax mRNA level(P<0.05, P<0.01)and up-regulated expression of Bcl-2 mRNA(P<0.05)were observed in primary hippocampal neurons in the above three GLGZG grous in comparison with that in the glutamate group. In addition, the protein expression is similar with mRNA, the down-regulated expression of Caspase-3, Bax protein(P<0.05, P<0.01), and up-regulated expression of Bcl-2 protein(P<0.01)were observed in hippocampal tissues of rats.Conclusion:GLGZG has protective effects on neurons in ischemic stroke rats and primary hippocampal neurons and the potential mechanism of GLGZG may be related to its anti-apototic function.